New perspectives in coronary heart disease management - V. I. Makolkin (Кардиоваскулярная терапия и профилактика, 2005)
The article is devoted to ACE inhibitor therapy in stable coronary heart disease (CHD). The author analyzes the results of multi-center trials on various ACE inhibitors’ efficacy in decreasing risk of all-cause mortality, fatal and non-fatal myocardial infarction, stroke, chronic heart failure in CHD patients. ACE inhibitor efficacy in CHD is explained by the influence on endothelial dysfunction, thrombosis and inflammation factors, increased bradykinin synthesis and NO-synthase activity. A new trail EUROPA demonstrated that perindopril (8 mg/d) could be recommended to patients with stable CHD.